A double-blind, randomized, multicenter, controlled study to evaluate the immunogenicity, safety, and tolerability of varicella vaccine (VARIVAX™) passage extension 34 (PE34) process administered concomitantly with measles, mumps, and rubella vaccine (M-M-R™ II) - Peter E. Silas; Edward N. Zissman; Julie Gardner; Shanjun Helian; Andrew W. Lee; Heather L. Platt (Taylor & Francis Group, 2020)
The varicella vaccine passage extension (VAR-PE) process was undertaken to extend the availability of varicella zoster virus (VZV)-containing vaccines. This study (V210-A03; NCT03239873) assessed the immunogenicity, safety, and tolerability of VAR-PE process in comparison with varicella vaccine commercial product 2016 (VAR) randomized 1:1 in 600 healthy children 12 to 23 months of age administered concomitantly with measles-mumps-rubella (MMR) vaccine. The VZV seroconversion rate at 6 weeks Postdose 1 in the PP population was 100% for both groups. VZV antibody response rates and GMTs of VZV antibodies to VAR-PE induced and were non-inferior to those induced by VAR 6 weeks Postdose 1. From Day 1 through Day 42, adverse events (AEs) were reported by 81.3% of participants Postdose 1 and 67.9% Postdose 2. From Day 1 through Day 42 Postdose 1, injection-site AEs related to varicella vaccine were reported by 31.1% and 29.7% of participants in VAR-PE and VAR, respectively, and Postdose 2, by 25.7% and 25.5% of participants in the VAR-PE and VAR groups, respectively. Systemic AEs were generally comparable for the 2 vaccination groups, with the exception of pyrexia and otitis media higher in VAR-PE, and diarrhea and teething higher in VAR. The incidence of systemic AEs was generally lower Postdose 2 compared with Postdose 1.